Chains of Adversity: The Time-Varying Consequences of Paternal Incarceration for Adolescent Behavior - Turney, Kristin (Journal of quantitative criminology, 2022)
Objectives I draw on general strain theory, a framework often used to understand adolescent behavior, and augment it with aspects of the stress process perspective to examine the time-varying consequences of paternal incarceration for adolescent behavior. Methods I use six waves of data from the Fragile Families and Child Wellbeing Study, a cohort of children born around the turn of the twenty-first century, and inverse probability of treatment weighting models to estimate the time-varying relationship between paternal incarceration and adolescent behavior problems and the mechanisms underlying this relationship. Results Results document three main findings. First, adolescents exposed to paternal incarceration at any point in the life course have more behavior problems than their counterparts not exposed to paternal incarceration. Second, exposure to paternal incarceration during early childhood, but not during middle childhood or early adolescence, is positively associated with behavior problems. Third, this relationship is partially explained by family adversities stemming from paternal incarceration. Conclusions This research builds on our criminological understanding of how strains, such as paternal incarceration, can facilitate inequalities in adolescent behavior by considering dynamic selection into paternal incarceration, the time-varying repercussions of paternal incarceration, and the mechanisms linking paternal incarceration to adolescent behavior. Early life course paternal incarceration facilitates chains of adversity that accumulate throughout early childhood, middle childhood, and adolescence.